2019
DOI: 10.1029/2019gl082136
|View full text |Cite
|
Sign up to set email alerts
|

Retrieving Precipitable Water Vapor From Shipborne Multi‐GNSS Observations

Abstract: Precipitable water vapor (PWV) is an important parameter for climate research and a crucial factor to achieve high accuracy in satellite geodesy and satellite altimetry. Currently Global Navigation Satellite System (GNSS) PWV retrieval using static Precise Point Positioning is limited to ground stations. We demonstrated the PWV retrieval using kinematic Precise Point Positioning method with shipborne GNSS observations during a 20‐day experiment in 2016 in Fram Strait, the region of the Arctic Ocean between Gre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
8
1
1

Relationship

4
6

Authors

Journals

citations
Cited by 53 publications
(33 citation statements)
references
References 32 publications
(34 reference statements)
2
30
0
1
Order By: Relevance
“…This makes it possible to predict short-term extreme weather events. For example, several scholars suggested that water vapor retrieved from GNSS could achieve a 1-3 mm accuracy [10][11][12][13], thus GNSS has been widely used in meteorological researches. Many previous studies for extreme weather events were mainly related to the spatio-temporal distribution and variability of water vapor, and even in the field of precipitation forecasting [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…This makes it possible to predict short-term extreme weather events. For example, several scholars suggested that water vapor retrieved from GNSS could achieve a 1-3 mm accuracy [10][11][12][13], thus GNSS has been widely used in meteorological researches. Many previous studies for extreme weather events were mainly related to the spatio-temporal distribution and variability of water vapor, and even in the field of precipitation forecasting [14][15][16][17].…”
Section: Introductionmentioning
confidence: 99%
“…Global wet delay and PWV data with high accuracy could be derived from the global navigation satellite system (GNSS) observations [28]. Moreover, ship-borne GNSS data could also supplement open-ocean validation [29,30]. Therefore, the calibration and validation model based on GNSS can monitor HY-2A CMR products with high temporal resolution and furtherly serve the application of HY-2A data in marine science, which is also the future work.…”
Section: Discussionmentioning
confidence: 99%
“…Figure 4 shows the relation of the annual average ZTD and ellipsoidal height of each site, where sites are separated into five groups according to site latitudes and each group is represented by different color, and all the sites are defined as the sixth group. For each group, the relation between annual average ZTD at the site ellipsoidal height h (ZTD h ), and the annual average ZTD on the ellipsoid surface (ZTD e ), can be expressed as an exponential formula [36]:…”
Section: Ztd With the Ellipsoid As Reference Surfacementioning
confidence: 99%